2021
DOI: 10.1063/5.0064232
|View full text |Cite
|
Sign up to set email alerts
|

Role of transferred graphene on atomic interaction of GaAs for remote epitaxy

Abstract: Remote epitaxy is a recently discovered type of epitaxy, wherein single-crystalline thin films can be grown on graphene-coated substrates following the crystallinity of the substrate via remote interaction through graphene. Although remote epitaxy provides a pathway to form freestanding membranes by controlled exfoliation of grown film at the graphene interface, implementing remote epitaxy is not straightforward because atomically precise control of interface is required. Here, we unveil the role of the graphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 32 publications
(18 reference statements)
0
27
0
Order By: Relevance
“…Over recent years, an emerging method named quasi-van der Waals (QvdW) epitaxy or remote epitaxy based on two-dimensional (2D) material has been proposed for high-quality heteroepitaxial growth of group-III nitrides 27 30 . The widely studied 2D material, graphene (Gr) has been incorporated as a buffer layer for the epitaxial growth of nitrides to effectively alleviate the lattice and TEC mismatches between the epilayer and the substrate 31 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Over recent years, an emerging method named quasi-van der Waals (QvdW) epitaxy or remote epitaxy based on two-dimensional (2D) material has been proposed for high-quality heteroepitaxial growth of group-III nitrides 27 30 . The widely studied 2D material, graphene (Gr) has been incorporated as a buffer layer for the epitaxial growth of nitrides to effectively alleviate the lattice and TEC mismatches between the epilayer and the substrate 31 33 .…”
Section: Introductionmentioning
confidence: 99%
“…1 f). Remote epitaxy of III-V materials requires several requirements: sufficiently thin graphene (monolayer) and clean graphene-substrate interface [ 11 , 12 ]. It was revealed that the polarity of the underlying substrates and the 2D material affects remote interaction through the 2D material, making relatively more strict requirements for remote epitaxy of III-V materials are necessary [ 13 ].…”
Section: Epitaxy On 2d-materials Coated Substratesmentioning
confidence: 99%
“…79,80 The ultrathin graphene layer allows remote interaction between substrates and epilayers, leading to the formation of crystalline epilayers that continues the substrate crystals. 81,82 GaAs NMs were released after removing graphene layer by wet or dry etching.…”
Section: Fabrication Processmentioning
confidence: 99%